The mark of slavery : disability, race, and gender in antebellum America - Barclay, Jenifer L. (Disability histories (Series), 2021)
"Time and again, antebellum Americans justified slavery and white supremacy by linking blackness to disability, defectiveness, and dependency. Jenifer L. Barclay examines the ubiquitous narratives that depicted black people with disabilities as pitiable, monstrous, or comical, narratives used not only to defend slavery but argue against it. As she shows, this relationship between ableism and racism impacted racial identities during the antebellum period and played an overlooked role in shaping American history afterward. Barclay also illuminates the everyday lives of the ten percent of enslaved people who lived with disabilities. Devalued by slaveholders as unsound and therefore worthless, these individuals nonetheless carved out an unusual autonomy. Their roles as caregivers, healers, and keepers of memory made them esteemed within their own communities and celebrated figures in song and folklore. Prescient in its analysis and rich in detail, 'The Mark of Slavery' is a powerful addition to the intertwined histories of disability, slavery, and race"--